Considerations on IASB Recent Issued Standards (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Recent financial crisis has raised numerous dilemmas around the accounting information relevance. History has drawn a clear trend in favour of international accounting convergence. The solution of IFRS, accepted as a global set of accounting standards, seems to be the proper solution for all players of the markets. The standard-setting mechanisms promoted by IASB encourage an increasing number of countries to adopt IFRS, in different ways. But questions remain regarding several controversial accounting areas such as impairment of assets, provisions, off-sheet accounting, fair value, fiscal impact on accounting treatments and so on. This article tries to reveal several aspects regarding IASB efforts on drawing a strategy of continuous improvement focused on increasing transparency and trust in financial reports. The article aim to make a short review about the main projects of research finalised by IASB, in cooperation with FASB and other national accounting regulators.